2018
DOI: 10.3126/jnhrc.v15i3.18847
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence and its Associated Factors among Nurses

Abstract: Background: Workplace violence among nurses is prevalent worldwide. If nurses become aware of the workplace violence and its risk factors then only they can protect themselves. This study assessed the prevalence of workplace violence and its associated factors among nurses in Pokhara, Nepal. Methods: A hospital-based descriptive cross-sectional study was conducted in Pokhara. The required sample size of the study was 200 nurses. We adopted self-administered questionnaire developed by International Labor Office… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
48
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 17 publications
(38 reference statements)
11
48
2
1
Order By: Relevance
“…Studies conducted in various parts of the world have also reported that nurses frequently experienced verbal abuse from patients’ relatives. 1,4,9,12,17,20 However, some studies are in contrast with our finding and reported nurse colleagues, 21 physicians, 18 and patients 6 as the main source of verbal abuse. The variation in sources of verbal abuse might be because of the different care culture existing in different countries.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in various parts of the world have also reported that nurses frequently experienced verbal abuse from patients’ relatives. 1,4,9,12,17,20 However, some studies are in contrast with our finding and reported nurse colleagues, 21 physicians, 18 and patients 6 as the main source of verbal abuse. The variation in sources of verbal abuse might be because of the different care culture existing in different countries.…”
Section: Discussioncontrasting
confidence: 99%
“…16 They found verbal abuse as the most prevailing types of violence, however, they did not specify about the verbal abuse among nurses. There is only one study about the prevalence of workplace violence among hospital nurses in Nepal, 17 which found that verbal abuse was reported by higher proportion than physical and sexual abuse. Therefore, the purpose of this study was to investigate the characteristics of verbal abuse encountered by nurses working in the hospital of Nepal and examine the association of sociodemographic and work-related characteristics such as their role in organization, ward in which the nurses was employed, working shift, and so on with verbal abuse incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the age, the study results revealed that the highest percentage of the study subjects within the age group (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) years, this finding consistent with (17) who reported that the highest percentage of the nurses in the emergency departments within age groups (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) years. Concerning the gender, the study results revealed that the majority of the study subjects are males.…”
Section: Discussionsupporting
confidence: 84%
“…The study findings revealed that there was a statistically significant positive correlation between nurses' age and their likelihood of exposure to violence in the future. This finding supported by that of (24) reported that there was a statistically significant positive relationship between nurses' age and their likelihood of exposure to violence in the future. The study findings revealed that there was a statistically significant inverse correlation between nurses' years of experience in nursing and risk of violence.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation